STRATEGI PENINGKATAN AKUNTABILITAS KINERJA INSTANSI PEMERINTAH KOTA BOGOR - Raharja, Enditya Luhur; Baga, Lukman M; Falatehan, A. Faroby (Jurnal Manajemen Pembangunan Daerah, 2018)
ABSTRACTIn the last few years the level of performance accountability of the Bogor City Government has not shown a significant increase, so it needs strategies to improve it. This research included descriptive research type with using primary and secondary data. Analysis methods used were Importance Performance Analysis, and Analytical Hierarchy Process. The purpose of this research were to analyze the weaknesses of the implementation of the performance accountability system of the Bogor City Government, and formulate the strategies to improve the performance accountability of the Bogor City Government. Based on the results of the Importance Performance Analysis showed that there are 7 attributes that become weaknesses of the implementation of the performance accountability system of the Bogor City Government. These attributes are alignment between planning documents, results-oriented performance planning, linkages of programs / activities with strategic planning, preparation of individual performance indicators, tiered performance measurement, and utilization of performance measurement. The strategy to improve the performance accountability of the Bogor City Government is strengthening commitment, implementing performance-based budgeting, SAKIP coaching, and improving the quality of APIP.Keywords: performance, accountabilityABSTRAKTingkat akuntabilitas kinerja Pemerintah Kota Bogor dalam beberapa tahun terakhir belum menunjukkan peningkatan yang signifikan, sehingga dibutuhkan strategi untuk peningkatannya. Penelitian ini termasuk jenis penelitian deskriptif dengan menggunakan data primer dan data sekunder. Metode analisis yang digunakan adalah Importance Performance Analysis, dan Analytical Hierarchy Process. Tujuan penelitian ini adalah untuk menganalisis kelemahan-kelemahan dalam penerapan sistem akuntabilitas kinerja Pemerintah Kota Bogor, dan merumuskan strategi peningkatan akuntabilitas kinerja Pemerintah Kota Bogor. Hasil penelitian menunjukkan bahwa terdapat 7 atribut yang menjadi kelemahan penerapan sistem akuntabilitas kinerja Pemerintah Kota Bogor. Atribut tersebut adalah keselarasan antar dokumen perencanaan, perencanaan kinerja berorientasi hasil, keterkaitan program/kegiatan dengan renstra, penyusunan indikator kinerja individu, pengukuran kinerja berjenjang, dan pemanfaatan pengukuran kinerja. Strategi untuk meningkatkan akuntabilitas kinerja Pemerintah Kota Bogor adalah penguatan komitmen, penerapan anggaran berbasis kinerja, pembinaan SAKIP, serta peningkatan kualitas APIP.Kata kunci: kinerja, akuntabilitas